COMPARISON OF OPENNESS TO EXPERIENCE IN MANAGERS AND NON-MANAGERS EMPLOYED AT MEAT INDUSTRY ‘OVAKO’ VISOKO, BOSNIA AND HERZEGOVINA - Goran Riđić; Minela Ahmić; Ognjen Riđić; Senad Bušatlić (Economic Review)
This primary research was conducted in order to find out what was the level of managers’ and employees’ openness to experience. In addition to this, this research will try to answer the question as to; are there any differences between the managers and non-managers or employees of a certain industry, in terms of openness to experience. It additionally covers the enduring characteristics, in other words, the big five personality traits, where Openness to Experience is to be one of those traits and the main emphasis is placed particularly on it. This research project is based on extensive literature review and previous works related to the openness to experience. Quantitative research design was applied with cross-sectional time frame at the end of Summer and beginning of Fall, 2015. The original-primary research has been conducted at the meat industry OVAKO, one part of AKOVA Impex. Quantitative survey instrument originally developed by Oregon Research Institute was adopted as a basis and was modified to meet statistical criteria for this research. Selection process was simple random sampling, which means that every single individual had the equal opportunity to be selected. Survey questions were distributed to 200 participants. From the sampling frame, 130 participants formed sample and the rest of 70 questionnaires were not completely filled out. The study found out that there was no statistically significant difference between the managers and non-managers in terms of openness to experience at meat industry OVAKO, Visoko.